Cholangiopathy in critically ill patients surviving beyond the intensive care period: a multicentre survey in liver units. Issue 11 (11th October 2017) - Laurent, L.; Lemaitre, C.; Minello, A.; Plessier, A.; Lamblin, G.; Poujol‐Robert, A.; Gervais‐Hasenknopf, A.; Pariente, E.‐A.; Belenotti, P.; Mostefa‐Kara, N.; Sogni, P.; Legrand, M.; et al.
Summary: Background: The outcome of cholangiopathy developing in intensive care unit (ICU) is not known in patients surviving their ICU stay. Aim: To perform a survey in liver units, in order to clarify the course of cholangiopathy after surviving ICU stay. Methods: The files of the liver units affiliated to the French network for vascular liver disease were screened for cases of ICU cholangiopathy developing in patients with normal liver function tests on ICU admission, and no prior history of liver disease. Results: Between 2005 and 2015, 16 cases were retrieved. Extensive burns were the cause for admission to ICU in 11 patients. Serum alkaline phosphatase levels increased from day 11 (2‐46) to a peak of 15 (4‐32) × ULN on day 81 (12‐511). Magnetic resonance cholangiography showed irregularities or frank stenosis of the intrahepatic ducts, and proximal extrahepatic ducts contrasting with a normal aspect of the distal common bile duct. Follow‐up duration was 20.6 (4.7‐71.8) months. Three patients were lost to follow‐up; 2 patients died from liver failure and no patient was transplanted. One patient had worsening strictures of the intrahepatic bile ducts with jaundice. Nine patients had persistent but minor strictures of the intrahepatic bile ducts on MR cholangiography, and persistent cholestasis without jaundice. One patient had normal liver function tests. Conclusions: In patients surviving their ICU stay, ICU cholangiopathy is not uniformly fatal in the short term or clinically symptomatic in the medium term. Preservation of the distal common bile duct appears to be a finding differentiating ICU cholangiopathy from other diffuse cholangiopathies. Abstract : Linked Content This article is linked to MacGilchrist paper. To view this article visithttps://doi.org/10.1111/apt.14441 .